Tło zmieszane z niczego. Problem nihilizmu u Witkacego - Sztaba, Wojciech (Wydawnictwo Naukowe UAM, 2014)
As Witkacy wrote in Narcotics, it is “the surrounding nothingness which creates a negative background for all being” that makes things visible. Nihilism provides a framework for Witkacy’s work. His philosophy and esthetics are a response to the nihilistic lack of meaning and the absolute, while his cultural pessimism is a projection of the lost paradise. The romantic attitude that he had developed by reading Schopenhauer and Nietzsche left deep traces in his art, thus generating the iconography of his paintings and permeating his dramas and novels.
A background created from nothing: The issue of nihilism in Witkacy’s works